Polychlorinated biphenyls: Hazardous properties and environmentally sound management in Ukraine - N. O. Ryzhenko; O. I. Bondar; V. V. Chetverykov; Y. O. Fedorenko (Regulatory Mechanisms in Biosystems, 2020)
Polychlorinated biphenyls are one of the most dangerous compounds for human health and the environment and are included to Annex C of the Stockholm Convention on Persistent Organic Pollutants. Since Ukraine joined the Stockholm Convention in 2007, the National Implementation Plan of the Stockholm Convention provides the environmentally sound disposal of polychlorinated biphenyls, as well as creation of a monitoring system and sharing information about toxicants. Polychlorinated biphenyls’ have fire resistance, low volatility and stability. Therefore, these substances have been widely used in industry, but on the other hand, they are a problem for the environment. The main hazardous properties of polychlorinated biphenyls are bioaccumulation, stability in the environment, the possibility of formation in accidents (especially in fires) of extremely persistent and toxic aromatic compounds, such as dioxins and furans. Toxic responses to polychlorinated biphenyls are: acute lethality; body weight loss; carcinogenesis; dermal toxicity; fatty liver; genotoxicity; hepatomegaly; immunosuppressive effects; neurotoxicity; porphyria; reproductive and developmental toxicity; thymic atrophy; thyroid hormone-level alterations. The most likely risks of polychlorinated biphenyls contamination in Ukraine are in the areas of operation, repair or storage of electrical equipment. According to quantity, the leading regions for accumulated polychlorinated biphenyls in Ukraine, are Dnipropetrovsk (459 tons), Volyn (280 tons) and Kyiv regions (255 tons). A comprehensive approach to reducing the risk of polychlorinated biphenyls for human health and the environment involves the improvement of the regulatory framework for managing in all stages of “life cycle”. Obtaining complete and accurate information on the volumes and forms of polychlorinated biphenyls accumulation and creation of modern effective technological support for polychlorinated biphenyls’ degradation are a necessary part of environmentally sound management of polychlorinated biphenyls in Ukraine. The “Polychlorinated Biphenyls Database in Ukraine” information system (2017) was created as a National Polychlorinated Biphenyls Registry in Ukraine. It was designed to systematize, structure, and analyze the large amount of information collected during the inventorising of polychlorinated biphenyls. The best technology of polychlorinated biphenyls degradation must not only provides a high degree of polychlorinated biphenyls’ destruction, but also not lead to the formation of new toxic compounds.